Fault diagnosis of gear transmissions via optic Fiber Bragg Grating strain sensors. (15th April 2022) - Bachar, Lior; Klein, Renata; Tur, Moshe; Bortman, Jacob
Highlights: Using optic Fiber Bragg Grating (FBG) strain sensors for gear diagnostics. Experimental study on two different test rigs – spur gear and helical gear. Comparison between strain and acceleration measurements at different operating conditions. Examination of the behavior of tooth faults in the vibration signature. A novel diagnostics methodology, including signal processing, CI's & HI analysis. Abstract: Most of the diagnostics approaches for health monitoring of gear transmissions, to date, are based on vibration analysis. A comprehensive research referring to applications of optic Fiber Bragg Grating (FBG) strain sensors for gear diagnostics is presented. The paper opens with a detailed literature review about fault diagnosis of gear transmission based on strain measurements. It is shown that diagnosis of spur and helical gears is feasible and yields similar capabilities compared to acceleration analysis. A novel diagnostic methodology based on FBG strain sensors is developed, justified, and experimentally validated for both gear types at different operating conditions, e.g., speed and load, and for local faults of different severities. The proposed methodology covers all the diagnostics stages, starting with a unique flow of signal processing, examination of condition indicators and finally, a definition of a Health Indicator (HI).